Energy diagnosis of the Maxxi building - Pena Soares de Oliveira, Alisson; Bravin Donadel, Clainer; Arthur Firmino Monhol, Filipe (Latin American Journal of Energy Research, 2021)
The search for improvements in energy efficiency of buildings has been a very current issue. This subject is relevant both for the potential of combining energy savings with cost reduction, and for setting an example of good practices for society and the market. This research identified opportunities for improvements in energy efficiency in the Maxxi building, headquarters of EDP / ES, an energy concessionaire in the state of Espírito Santo. The case study data will be collected through unstructured interviews and technical visits, and through examination of related documentation and standards. The possibility of obtaining energy gains was evaluated and solutions were proposed for the opportunities found. The payback time with analysis of the investment required for some improvements was calculated.